2007
DOI: 10.1128/jcm.00234-07
|View full text |Cite
|
Sign up to set email alerts
|

Exceptionally High Representation of Burkholderia cepacia among B. cepacia Complex Isolates Recovered from the Major Portuguese Cystic Fibrosis Center

Abstract: Burkholderia cepacia , a species found infrequently in cystic fibrosis (CF), was isolated from 85% of patients infected with bacteria of the B. cepacia complex that visited the major Portuguese CF center, in Lisbon, during 2003 to 2005. A detailed molecular analysis revealed that this was mainly due to two B. cepacia clones. These clones were indistinguishable from two strains isolated from intrinsically contaminated nonsterile saline solutions for na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
75
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(78 citation statements)
references
References 23 publications
3
75
0
Order By: Relevance
“…Vandamme and A. Baldwin, unpublished data). Moreover, several cases of epidemic transmission of taxon K strains among cystic fibrosis patients have been reported (Campana et al, 2005;Cunha et al, 2007). The wholegenome sequences of two taxon K strains, namely Burkholderia sp.…”
Section: Introductionmentioning
confidence: 99%
“…Vandamme and A. Baldwin, unpublished data). Moreover, several cases of epidemic transmission of taxon K strains among cystic fibrosis patients have been reported (Campana et al, 2005;Cunha et al, 2007). The wholegenome sequences of two taxon K strains, namely Burkholderia sp.…”
Section: Introductionmentioning
confidence: 99%
“…The epidemiological surveillance of Bcc bacteria in respiratory infections at the major Portuguese CF center of Hospital de Santa Maria (HSM), in Lisbon, identified an exceptionally high representation of B. cepacia species isolates. This fact was attributed to contamination of saline solutions for nasal application (24). Recently, after reexamination of the B. cepacia clinical isolates from the Institute for Bioengineering and Biosciences, Instituto Superior Técnico (iBB/IST) collection, isolates of the recA RFLP type K, formerly classified as B. cepacia species (24,25), and some additional isolates were classified as B. contaminans (17).…”
mentioning
confidence: 99%
“…A total of 108 isolates of B. cepacia (n ϭ 83) and B. contaminans (n ϭ 25), obtained at the Portuguese CF treatment center at HSM, in Lisbon, including 35 isolates obtained from contaminated nonsterile saline solutions for nasal application, were used in this study (Table 1) (17,24,25). The isolates had been obtained during the past 2 decades and were characterized molecularly at the iBB/ IST by sequencing analyses of the recA gene (17,(24)(25)(26)(27).…”
mentioning
confidence: 99%
“…In general, B. cenocepacia predominates, followed by Burkholderia multivorans (2,4,5,31,33,44). However, the species B. cepacia, found infrequently in CF patients worldwide, has an exceptionally high representation among the BCC isolates in Portugal, accounting for one-half of the number of the isolates retrieved from 1995 to 2006 (12). Intrinsically contaminated saline solutions for nasal application and the environment are likely sources for B. cepacia infection (12).…”
mentioning
confidence: 99%
“…However, the species B. cepacia, found infrequently in CF patients worldwide, has an exceptionally high representation among the BCC isolates in Portugal, accounting for one-half of the number of the isolates retrieved from 1995 to 2006 (12). Intrinsically contaminated saline solutions for nasal application and the environment are likely sources for B. cepacia infection (12). During the epidemiological survey carried out in Portugal, it was found that B. cepacia isolates may also be involved in the progressive deterioration of the CF lung during persistent infection (11).…”
mentioning
confidence: 99%